Effect of biofilm phenotype on resistance of Gardnerella vaginalis to hydrogen peroxide and lactic acid - PATTERSON, Jennifer L. (2007)
OBJECTIVES: Bacterial vaginosis (BV) is the most common vaginal disorder worldwide. Certain lactobacilli produce H(2)0(2) and lactic acid, which normally suppress growth of anaerobes, but in BV, G. vaginalis and other anaerobes proliferate, and the number of lactobacilli decreases. Gardnerella vaginalis colonizes the vaginal epithelium as a biofilm, which likely plays a role in colonization and relapsing infection. STUDY DESIGN: We developed an in vitro model for G. vaginalis biofilm formation, and compared susceptibilities of biofilms vs. planktonic cultures to H(2)O(2) and lactic acid. The structure and composition of the biofilm matrix were studied in order to design a method for biofilm dissolution. RESULTS: Biofilms tolerated 5-fold and 4–8 fold higher concentrations of H(2)O(2) and lactic acid (respectively) than planktonic cultures. Proteolytic dissolution of biofilms reduced sensitivity to H(2)0(2) and lactic acid. CONCLUSIONS: Increased tolerance to H(2)O(2) and lactic acid suggests that biofilm formation contributes to survival of G. vaginalis in the presence of lactobacilli.